A Dual Repeat Cis-Element Determines Expression of GERANYL DIPHOSPHATE SYNTHASE for Monoterpene Production in Phalaenopsis Orchids - Chuang, Yu-Chen; Hung, Yi-Chu; Hsu, Chi-Yu; Yeh, Chuan-Ming; Mitsuda, Nobutaka; Ohme-Takagi, Masaru; Tsai, Wen-Chieh; Chen, Wen-Huei; Chen, Hong-Hwa (Frontiers in Plant Science, 2018)
Phalaenopsis bellina is a scented orchid emitting large amount of monoterpenes. GERANYL DIPHOSPHATE SYNTHASE (PbGDPS) is the key enzyme for monoterpene biosynthesis, and shows concomitant expression with the emission of monoterpenes during flower development in P. bellina. Here, we identified a dual repeat cis-element in the GDPS promoter that is critical for monoterpene biosynthesis in Phalaenopsis orchids. A strong correlation between the dual repeat and the monoterpene production was revealed by examination of the GDPS promoter fragments over 12 Phalaenopsis species. Serial-deletion of the 2-kb GDPS promoter fragments demonstrated that the integrity of the dual repeat was crucial for its promoter activities. By screening the Arabidopsis transcription factors (TFs) cDNA library using yeast one-hybrid assay, AtbZIP18, a member of group I of bZIP TFs, was identified to be able to bind the dual repeat. We then identified PbbZIP4 in the transcriptome of P. bellina, showing 83% identity in the DNA binding region with that of AtbZIP18, and the expression level of PbbZIP4 was higher in the scented orchids. In addition, PbbZIP4 transactivated the GDPS promoter fragment containing the dual repeat in dual luciferase assay. Furthermore, transient ectopic expression of PbbZIP4 induced a 10-fold production of monoterpenoids in the scentless orchid. In conclusion, these results indicate that the dual repeat is a real TF-bound cis-element significant for GDPS gene expression, and thus subsequent monoterpene biosynthesis in the scented Phalaenopsis orchids.